Pricing strategy and tariff structure for a port authority: a case study of South Africa. Issue 6 (18th August 2018) - Gumede, Sanele; Chasomeris, Mihalis
ABSTRACT: South Africa's Transnet National Ports Authority's (TNPA) tariff structure shows imbalances and cross-subsidisation amongst commodities and groups of port users. Benchmarking studies show that South African port costs are below the benchmarked mean for low-value bulk commodities like coal and iron ore, and above the mean for high-value containerised commodities. Vessel charges are also below the benchmarked mean and the required tariff revenues are raised from the tariffs charged to port tenants and cargo owners. This study examines and compares the 2013/2014 TNPA tariff structure with that proposed by the Ports Regulator of South Africa. It compiles, calculates and compares 254 commodity cargo dues with their relevant sector base tariffs for the year. The results indicate the level and direction of cross-subsidisation within and between break-bulk, dry bulk, liquid bulk and containerised cargoes. Of the 254 commodities examined, 100 are below the sector base tariff (being subsidised) and 154 are above (subsidising other cargoes). The findings of this article contribute to the implementation and monitoring of a tariff strategy that will allow for a more reasonable, just and cost reflective TNPA tariff structure.